Problems Connected with the Determination of the Sum Insured in the Insurance of Immovables (Dwelling Houses and Flats) in the Context of the Application of the Proportion Clause - Tomaszkiewicz, Aneta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The importance of insurance is the greater, the more effectively it fulfills its compensatory function. However, if the compensation is paid at the level that does not allow for compensation for the whole damage, compensating it only partially, this insurance only partially can fulfill its economic and social function. When the sum insured is equal to the insured value, the insured subject is covered to the full value, and such insurance is compliant with the principle of the full insurance coverage.Determination of the appropriate value of the immovables may be too difficult for an average customer, hence the insurance companies, as professionals, could advise the customer when signing the contract, so that the client can consciously decide about the level of the sum insured. If the customer does not understand the rules for determining the sum insured and the payment of compensation, it may result in an irreparable damage to the image of the insurance company, if it limits the damages due to the need to apply the principle of proportionality. The admissibility of the application of this principle also raises doubts among practitioners. It should be noted, however, that both the client and the insurance company is preferred to maintain the principle of the full coverage when the company receives a premium according to the sum insured, which is the actual value of the property and the customer receives full compensation, as there is no need to use the proportion clause.